Implementation of strategies to improve nutritional intervention for patients with cancer treatment-related oral mucositis: a best practice implementation project. Issue 4 (5th December 2021) - Zhang, Lanfang; Zhou, Chunlan; He, Ling; Wu, Yanni; Xie, Guozhu; Chen, Peijuan
ABSTRACT: Background: Oral mucositis is a common complication after radiotherapy or chemotherapy in cancer patients. Oral mucositis can affect the patient's food intake and their confidence in treatment as patients are more likely to suffer severe pain, experience weight loss, encounter an interruption or change of cancer treatment plan, and are reported to have a reduced survival from the disease. Nutritional intervention is the primary nursing focus in patients with oral mucositis treated by chemoradiotherapy. Objectives: The current best practice implementation project aimed to establish best practice principles in nutritional interventions for patients with cancer treatment-related oral mucositis. Methods: This was an evidence-based audit and feedback project that used a three-phase approach at a public hospital in China. Phase 1 involved developing five evidence-based audit criteria informed by current best available evidence, and undertaking a clinical audit of current practice on 50 patients in the Department of Radiation Oncology of Nanfang Hospital using the JBI's Practical Application of Clinical Evidence System. Phase 2 utilized the Getting Research into Practice component of the Practical Application of Clinical Evidence System to identify barriers to compliance with best practice principles and developed strategies and resources to improve compliance. Phase 3 involved conducting a postaudit using the same sample size and audit criteria to re-evaluate compliance with best practice. Results: Baseline results showed that compliance rates were 0% for criteria 1 and 2, 76% for criteria 3 and 5, and 82% for criterion 4. The implementation of strategies, including establishing a multidisciplinary team with a dietitian, creating training and education programs for all staff and patients, utilizing a scale regarding diet to assess patients' current diet, and establishing a nutrition intervention nursing procedure to supervise implementation of the nutritional intervention for patients with cancer treatment-related oral mucositis, increased compliance with best practice, achieving compliance rates of at least 82% for all five audit criteria. Conclusion: The implementation of context-specific strategies improved compliance with evidence-based practice in the nutritional intervention for patients with cancer treatment-related oral mucositis. Sustainability of best practice is important, with further audits planned to evaluate the sustainability of these practice changes.